SISTEM INFORMASI AKADEMIK PADA SEKOLAH SMA NEGERI 1 NUBATUKAN LEMBATA BERBASIS WEBSITE - Jago Belalawe, Benyamin (HOAQ (High Education of Organization Archive Quality) : Jurnal Teknologi Informasi, 2021)
Public High School 1 Nubatukan Lembata is one of the institutions engaged in education in Lembata Regency. The process of delivering information to Public High School 1 Nubatukan such as value information, lesson schedules, student data, teacher data, student guardian or parent data, extracurricular data, announcements, subject data and data have not been computerized, meaning that information delivery is still carried out orally or pasted on a bulletin board and this can result in delays in delivering information and work processes that are less effective and efficient can hinder the performance of these educational institutions. Data collection techniques used in this study are interviews, literature study, observation and questionnaires, making this application using Adobe Dreamweaver and MysQl database. The results of this study concluded that a web-based school information system was created and applied the application to assist schools in delivering effective school information